PENERAPAN METODE POLINOM NEWTON GREGORY MAJU DAN POLINOM NEWTON GREGORY MUNDUR DENGAN METODE HAMILTON-PERRY DALAM MEMPREDIKSI JUMLAH PENDUDUK SUMATERA UTARA. - Ratna Wahyuni; Indah Simamora (Universitas Quality, 2019)
Population data needs are absolute things that must be met by BPS, but the most complete source of population data comes from population census results. Meanwhile, the implementation of the population census is only once every 10 years because it requires cost, time, and energy. Population prediction in the following year in each census period needs to be done to determine the difference in population growth in that year. Therefore, researchers are interested in studying the